MENGEMBANGKAN BRANDING DESA WISATA NYARAI MELALUI VIDEO PROMOSI DENGAN TEKNIK-TEKNIK EDITING YANG MENARIK - Robby Usman; Widia Marta (Universitas Mataram, 2023)
Desa Wisata Nyarai in Padang Pariaman Regency, West Sumatra, is a tourist destination that has natural beauty and interesting cultural wealth to explore. However, Desa Wisata Nyarai has not been able to optimally promote its potential so that tourist visits are still relatively low. Therefore, the development of innovative branding and promotion needs to be done to introduce Des to potential tourists. This lecturer service aims to develop the branding and promotion of the Desa Wisata Nyarai through making attractive and innovative promotional videos. The promotional video showcases the beauty and diversity of Desa Wisata Nyarai, as well as introduces the superior products owned by the tourist village. Interesting and innovative editing techniques such as the use of music, special effects, and animation are used to make promotional videos more attractive and attract the attention of potential tourists. After the promotional video is finished, an evaluation is made of the attractiveness and branding impression created from the video. The evaluation results show that promotional videos with interesting and innovative editing techniques can increase the attractiveness and branding impression of Nyarai. It is hoped that the use of promotional videos with interesting and innovative editing techniques can increase the number of tourist visits to Desa Wisata Nyarai and ultimately provide economic benefits for the local community.